National approaches to the vaccination of recently arrived migrants in Europe: A comparative policy analysis across 32 European countries. Issue 27 (January 2019) - Ravensbergen, Sofanne J.; Nellums, Laura B.; Hargreaves, Sally; Stienstra, Ymkje; Friedland, Jon S.; ,
Abstract: Background: Migrants may be underimmunised and at higher risk of vaccine-preventable diseases, yet there has been no comprehensive examination of what policies are currently implemented across Europe targeting child and adult migrants. We analysed vaccination policies for migrants in 32 EU/EEA countries and Switzerland. Methods: Using framework analysis, we did a comparative analysis of national policies and guidelines pertaining to vaccination in recently arrived migrants through a systematic guideline and literature review and by approaching national experts. Results: Six (18.8%) of 32 countries had comprehensive policies specific to the vaccination of migrants (two focused only on child migrants, four on both adults and children). Nineteen (59.4%) countries applied their national vaccination schedule for migrant vaccinations, predominantly focusing on children; and five (15.6%) countries had circulated additional migrant-specific resources to relevant health-care providers. In six (18.8%) countries, policies on migrant vaccination focused on outbreak-specific vaccines only. In ten (31.3%) countries, policies focused on priority vaccinations, with polio being the vaccine most commonly administered and heterogeneity noted in vaccines recommended to adults, adolescents, and children. Eighteen (56.3%) countries recommended that an individual should be considered as unvaccinated where vaccination records were missing, and vaccines re-administered. Nine (28.1%) countries reported that specific vaccinations were mandatory. Conclusion: There is considerable variation in policies across Europe regarding approaches to vaccination in adult and child migrants, and a lack of clarity on optimum ways forward, what vaccines to offer, with a need for robust research in this area. More emphasis must be placed on ensuring migrant-specific guidance is disseminated to front-line healthcare professionals to improve vaccine delivery and uptake in diverse migration populations across the region.